Exploratory Analysis of Psychological Competencies in the Clinical Domain of University Students from an Interbehavioral Perspective - Zavala Peralta, Jonathan (2025)
Background: Higher Education Institutions (HEIs) seek to foster in students the development of professional competencies, that is, behaviors that conform to the fulfillment of the criteria of their respective disciplinary fields. From an interbehavioral perspective, the evaluation of these competencies involves defining behavioral indicators that allow their learning to be verified. The present study focuses on three fundamental competencies that comprise a large part of the clinical psychologist’s skills (identification of relevant cases, diagnostic assessment, intervention planning). Objective: To evaluate professional competencies in the clinical domain in students from UNAM. Method: Forty psychology students participated (16 from the fifth semester and 24 from the seventh semester). A modified version of the Virtual Environment for the Development and Evaluation of Professional Competencies in Psychologists (EVACOMPS; Cruz, 2022) was used, composed of twenty-one exercises organized into different types of performance. Results: On average, seventh-semester students obtained 60% correct answers, and fifth-semester students 50%, differences that were statistically significant. In the identification of relevant cases, the highest percentage of incorrect answers was found in both groups. Conclusions: While it is necessary to expand the sample, the modified EVACOMPS is a relevant tool for evaluating professional performance in the clinical domain of psychology. The low percentages of correct answers show the need to develop strategies to address the academic deficiencies that students carry since the beginning of their studies.